Incidence of Color Blindness among Undergraduates Students of Medical College in Pokhara - Shrestha, Ripti; Yadav, Bijendra Prasad; Amatya, Neebha; Rana, Rajab; Prajapati, Rajesh (Birat Journal of Health Sciences, 2022)
Introduction: There are many genetic disorders that are X-linked, one being the color blindness. Some individuals affected with the disorders may remain unaware till detected for a long time. There are very few reports about the incidence of the color blindness among the medical undergraduate students. Objectives: Ojective of our study was to assess the color blindness incidence, among the medical undergraduates at the Gandaki Medical College, Pokhara. Methodology: We piloted an observational cross-sectional study among the first and second year medical students (MBBS, BDS, Nursing, and paramedics) at Gandaki medical college. We finalized 300 students of both the genders based on the inclusion criteria. We performed in the natural day light, the color vision test using the Ishihara plates. We assessed incidence, the type of the color blindness and the gender distribution among the subjects. We compared the data thus obtained applying the “chi square statistical test” deliberating p<0.05 as significant. Results: We observed that all the colorblind subjects in the study were male who constituted 2% of the all the subjects. There was significant difference statistically among the types of the color blindness with majority having Deuteranomaly. Conclusions: We can conclude that incidence of the color blindness was exclusive among men in our study. Total color blindness was seen in majority of the male subjects. Screening the students will enable the unaware students of their disability and hence they can be guided to proper counseling.